Performance evaluation of solar receiver heat exchanger with rectangular-wing vortex generators - Koolnapadol, Narin; Promvonge, Pongjet; Skullong, Sompol (My University, 2020)
The paper presents an experimental investigation on heat transfer and flow resistance in a solar air heater (SAH) duct with rectangular-wing vortex generators (RWVGs) on the absorber plate to increase the SAH system performance. The experimental work is carried out in the test duct with its aspect ratio (AR) of 10 for Reynolds number (Re) based on the hydraulic duct diameter ranging from 5290 to 22,700. The RWVGs are placed on the absorber with three attack angles (α=30°45°and 60°) and three relative wing pitches (PR = Pl/H = 1.0, 1.5 and 2.0) at a single relative wing height (BR=b/H=0.67). The experimental result shows that the use of RWVGs leads to the considerable increase in Nusselt number (Nu) over the flatplate duct (smooth duct) around 4.06-5.79 times while the increase in friction factor (f) is about 11.43-43.97 times. The Nu and f display the increasing trend with the rise of α but show the opposite trend for the increment of PR. The highest thermal performance for using the RWVG roughness is some 1.95 at α=30°and PR = 1.5. Correlations for Nu and f have also been developed and determined as a function of RWVG parameters.
Keywords: Flow resistance; Solar air heater; Thermal performance; Vortex generators